Implementasi Pendekatan Whole Language Anak Usia Dini Di Taman Kanak-Kanak - Damhud , Ayu Nanda Putri; Amanda (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2024)
It is commonly recognized that society typically reduces all facets of language acquisition to just reading and writing, a rather minor portion of language development. If used correctly and consistently, the whole language approach—let alone its application to early language learning can be a natural and enjoyable way to foster children's enthusiasm in literacy. Literacy has a big role in language learning in industrialized nations. The purpose of this study is to implement the entire language strategy in the Pgri Ketitanglor Kindergarten for young children. This study used action research, a form of quantitative study. On May 26, 2023, the study was carried out at PGRI Ketitanglor Kindergarten. Three kids between the ages of 5 and 6 served as the study's subjects, and their selection was based on the findings of observations, interviews, and document reviews. Because some kids have been able to write and read appropriately and correctly, the observation findings of the entire language method with eight components in the learning processes at Pgri Ketitanglor Kindergarten are said to be 80% successful. The other 20% of kids are still in the beginning stages of emerging or developing.